Metabolomics Analysis Provides New Insights Into the Molecular Mechanisms of Parasitic Plant Dodder Elongation in vitro - Zhang, Yuexia; Zhang, Yushi; Jiang, Linjian; Li, Zhaohu; Zhang, Mingcai (Frontiers in Plant Science, 2022)
Dodder (Cuscuta spp.) species are obligate parasitic flowering plants that totally depend on host plants for growth and reproduction, and severely suppress hosts growth. As a rootless and leafless plant, excised dodder shoots exhibit rapid growth and elongation for several days to hunt for new host stems and parasitization could be reestablished. This is one unique ability of dodder to facilitate its success in nature. Clearly, excised dodder stems have to recycle stored nutrients to elongate as more as possible. However, the mechanism of stored nutrients recycling in the in vitro dodder shoots is still poorly understood. Here, we found that dodder is a carbohydrate-rich holoparasitic plant. During the in vitro dodder shoots development, starch was dramatically and thoroughly degraded in the dodder shoots. Sucrose derived from starch degradation in the basal stems was transported to the shoot tips, in which EMP and TCA pathways were activated to compensate for carbon demand for the following elongation according to the variations of sugar contents, related crucial genes expression and the metabolomics analysis. Additionally, antioxidants were significantly accumulated in the shoot tips in contrast to those in the basal stems. The variations of phytohormones (jasmonic acid, indole-3-acetic acid, and abscisic acid) indicated they played essential roles in this process. All these data suggested that starch and sucrose degradation, EMP and TCA activation, antioxidants and phytohormones were crucial and associated with the in vitro dodder shoots elongation.